2005
DOI: 10.1038/sj.ijo.0803048
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of high-fat feeding and circadian desynchronization

Abstract: Objective: To assess whether circadian desynchronization leads to metabolic alterations capable of promoting dietary obesity and/or impairing glucose tolerance. Design: Rats fed either with chow pellets (i.e., low-fat diet with 4% mass of fat) or high-fat diet (34% mass of fat). Half of each diet group was exposed to a fixed light-dark cycle or to a 10-h weekly shift in the light-dark cycle from Thursday to Sunday (20 shifts). To enforce the shifted animals to be active at unusual times of the day, food was av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 31 publications
1
29
1
3
Order By: Relevance
“…24 A similar effect has been observed in rats. 25 Although previously shown in rats, 9 to our knowledge, a novel discovery from this study was the direct link between oestrus and running distance, which had not been reported earlier for laboratory mice. Earlier studies have shown that the female golden hamster runs further during preoestrus and oestrus than postoestrus, 26 whereas female rats run most before oestrus and least immediately after.…”
mentioning
confidence: 86%
“…24 A similar effect has been observed in rats. 25 Although previously shown in rats, 9 to our knowledge, a novel discovery from this study was the direct link between oestrus and running distance, which had not been reported earlier for laboratory mice. Earlier studies have shown that the female golden hamster runs further during preoestrus and oestrus than postoestrus, 26 whereas female rats run most before oestrus and least immediately after.…”
mentioning
confidence: 86%
“…A number of different types of high-fat and/or highenergy diets have already been used to induce obesity and/or mimic the human metabolic syndrome in rodents [12][13][14][15][16][17]. Most studies have used only one high-fat formula compared with the standard chow diet.…”
Section: Dietmentioning
confidence: 98%
“…[15]) or Long-Evans (e.g. [14,17]) rats. The increase in body mass obtained in the present study with both HFD1 (i.e.…”
Section: Figure 5 Plasma Adiponectin (A and B) And Leptin (C And D) Ementioning
confidence: 99%
“…Les effets délé-tères de la désynchronisation chronique sur la santé méta-bolique ont été identifiés chez les animaux. Les rats exposés à un changement bihebdomadaire du cycle lumière-obscurité pendant 3 mois sont en surpoids et présentent une diminution de la sécrétion d'insuline par rapport à des animaux maintenus dans un cycle lumière-obscurité fixe [28,29]. Une autre étude a également montré que la désynchronisa-tion circadienne par le jetlag chronique accélère la survenue du diabète chez des rats transgéniques qui développent un diabète de type 2 avec l'âge [30].…”
Section: Pathologieunclassified